Książę Józef Poniatowski w twórczości Kazimierza Bartoszewicza - Florczak, Ilona (Przegląd Nauk Historycznych, 2014)
Kazimierz Bartoszewicz (1852–1930), writer and historian, living in Krakow, Galicia, in his journalistic works dealt with the popularization of the history of the Polish nation. He was highly regarded by readers of participated Poland journalist and social activist. Among his articles were texts on the life and work of Joseph Poniatowski. Most works on nephew of Stanislaus Augustus wrote in 1913, that is, on the centenary of the death of Prince at the Battle of Nations at Leipzig, including the same in the nationwide celebration of this event. Under the influence of nineteenthcentury legend surrounding the figure of Prince Joseph, he was trying newly built national hero myth of Joseph Poniatowski. Like other writers and historians, especially in Galicia, in Bartoszewicz’ works, prince was not only an excellent leader and commander, full of youthful charm favorite ladies, but first and foremost a defender of honor of the Polish nation, faithful to the idea and the nation. These features, highlighted many times in press releases, literature, and finally backed up prior to the work of historians (especially in the biography of the Duke, author Simon Askenazy) made of Joseph Poniatowski figure worthy of inclusion in the pantheon of national heroes, particularly during the period when the Polish people again began to loudly talk about independence, and when he began to develop in Galicia Polish paramilitary movement, the members of the Prince Joseph was the best model.